Chemical intercalation of heavy metal, semimetal, and semiconductor atoms into 2D layered chalcogenides. (13th July 2018) - Wang, Mengjing; Williams, David; Lahti, Gabriella; Teshima, Samantha; Dominguez Aguilar, David; Perry, Russell; Koski, Kristie J
Abstract: A major outstanding challenge in the field of intercalation chemistry has been the insertion of heavy metals into a 2D layered material. Heavy metal intercalation is a promising route towards access of chemically tailored materials or enhancement of novel physics. We present a new series of wet chemical strategies to intercalate atomic heavy metal and semimetal species (Bi, Cr, Ge, Mn, Mo, Ni, Os, Pb, Pd, Pt, Rh, Ru, Sb, and W) into layered chalcogenides. Bismuth selenide, Bi2 Se3, and niobium diselenide, NbSe2, are used to demonstrate this chemistry. Atomic intercalation is performed in solution using decomposition of zero-valent coordination compounds at low temperatures (̃50 °C–170 °C) or reduction with tin chloride. This host of chemical routes is non-destructive, general for chalcogens, and can be used to intercalate some lighter elements as well. These intercalation reactions more than double the current number of atomic intercalants and give access to unique physical properties including heterostructures, charge density waves, and polytypic superlattice structures.